A cognitive accountability mechanism for penalizing misbehaving ECN‐based TCP stacks. (2nd April 2012) - Latré, Steven; de Meerssche, Wim Van; Deschrijver, Dirk; Papadimitriou, Dimitri; Dhaene, Tom; Turck, Filip De
SUMMARY: The introduction of high‐bandwidth demanding services such as multimedia services has resulted in important changes on how services in the Internet are accessed and what quality‐of‐experience requirements (i.e. limited amount of packet loss, fairness between connections) are expected to ensure a smooth service delivery. In the current congestion control mechanisms, misbehaving Transmission Control Protocol (TCP) stacks can easily achieve an unfair advantage over the other connections by not responding to Explicit Congestion Notification (ECN) warnings, sent by the active queue management (AQM) system when congestion in the network is imminent. In this article, we present an accountability mechanism that holds connections accountable for their actions through the detection and penalization of misbehaving TCP stacks with the goal of restoring the fairness in the network. The mechanism is specifically targeted at deployment in multimedia access networks as these environments are most prone to fairness issues due to misbehaving TCP stacks (i.e. long‐lived connections and a moderate connection pool size). We argue that a cognitive approach is best suited to cope with the dynamicity of the environment and therefore present a cognitive detection algorithm that combines machine learning algorithms to classify connections into well‐behaving and misbehaving profiles. This is in turn used by a differentiated AQM mechanism that provides a different treatment for the well‐behaving and misbehaving profiles. The performance of the cognitive accountability mechanism has been characterized both in terms of the accuracy of the cognitive detection algorithm and the overall impact of the mechanism on network fairness. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : This article presents an accountability mechanism that detects and penalizes misbehaving ECN based TCP stacks, which ignore congestion warnings. To detect misbehaving connections, a cognitive algorithm is presented that combines machine learning algorithms to classify connections into misbehaving and well‐behaving profiles. The performance of the cognitive accountability mechanism has been characterised both in terms of the accuracy of the detection algorithm and the impact of the mechanism on the network fairness.